PENGARUH SISTEM TATA NIAGA DAN HARGA TERHADAP KESEJAHTERAAN PETANI KARET DI KABUPATEN BALANGAN - Latte, Jumai (PPPM STIA Amuntai, 2019)
The objectives of this research are 1) to find the effect of system trade on price. 2) To find the effect of price on the welfare of the farmer rubber. 3) To fine the effect of sytem trade on the welfare of the farmer rubber. The Types of research is explanatory research. Populations and samples in this study are the farmer rubber at Kabupaten Balangan. A sample of 210 the farmer rubber and sample collection technique is accidental sampling. The analysis data technique in this research use SEM analysis which software Smart PLS version 2.0 M3. These results showed that 1) system trade significant effect on price with the effect of 72,20%. 2) Price significant effect on the welfare of the farmer rubber with the effect of 5,60%. 3) System trade significant effect on the welfare of the farmer rubber with the effect 21,50%.